ASPEK HUKUM WASIAT WAJIBAH UNTUK AHLI WARIS ANAK KANDUNG YANG BERBEDA AGAMA DALAM PUTUSAN MAHKAMAH AGUNG NOMOR 51 K/AG/1999 - Darmawan, Wahyu (Yustitia, 2021)
The barrier to inheritance or mawani 'al-irth is a barrier to the implementation of inheritance between the heir and his heirs. One of the barriers to the implementation of war is religious differences. Religious differences are one of the barriers that can cause a person to not be able to receive inheritance from someone who has died. The existence of these religious differences becomes a barrier to inheritance which has been explained based on a hadith of the Prophet Muhammad SAW: "It is not right for a Muslim to respect an infidel, nor do an infidel respect a Muslim" (HR Bukhari & Muslim). Research Methods in this scientific papers using normative juridical research methods and using data collection techniques carried out using descriptive analysis techniques, with secondary data sources, which include primary legal materials such as laws and regulations relating to the rights of children and wives in divorce cases, sued unseen husbands, as well as secondary legal materials such as books, journals, articles, and other legal doctrines. From the results of the research that has been done, it can be concluded that the position of non-Muslim children on the inheritance of heirs who are Muslim is not as heirs because Islamic Inheritance Law does not recognize the existence of heirs to people of different religions (nonMuslims).However, according to the Panel of Judges and, according to Islamic inheritance law, heirs who are not Muslim, cannot be heirs, but because Islamic inheritance law in Indonesia contains an egalitarian principle, relatives who are religious other than Islam who have blood relations with the heirs can get the share of inheritance by using a mandatory will without exceeding the share of heirs who are equal to it, this is in accordance with the Decision of the Supreme Court.